Expanded Transsphenoidal Trans-Lamina Terminalis Approach to Tumors Extending Into the Third Ventricle: Technique Notes and a Single Institute Experience - Cao, Lei; Wu, Wentao; Kang, Jie; Qiao, Hui; Yang, Xiaocui; Bai, Jiwei; Zhu, Haibo; Zhang, Yazhuo; Gui, Songbai (Frontiers in Oncology, 2021)
Objective The trans lamina terminalis approach (TLTA) has been described as a way to remove third ventricular tumors. The aim of this paper was to analyze the feasible outcomes of TLTA applied to tumors extending into the third ventricle in our institute. Methods Suprasellar tumors (n = 149) were treated by the extended endonasal approach from September 2019 to December 2020 in Beijing Tiantan Hospital. Eleven of the tumors were treated by TLTA or TLTA via the trans-chiasm-pituitary corridor (TCPC). The surgical technique notes of TLTA were described and indications and outcomes of the approach were analyzed. Results There were 11 patients enrolled in the study, six with papillary craniopharyngiomas, two with adamantinomatous craniopharyngiomas, one with a germinal cell tumor (GCT), one with cavernous malformation and one with chordoid glioma. Four of the patients received a radical resection by TLTA alone, while seven of them received TLTA via the TCPC. Gross total resection was achieved in eight patients (72.7%), and partial resection in three patients (27.3%). Visual function was improved in four of the 11 patients (36.4%), was unchanged in five patients (45.5%), and deteriorated in two patients (18.2%). New-onset hypopituitarism occurred in seven patients (63.3%) and new-onset diabetes insipidus occurred in two patients (18.2%). Electrocyte imbalance were observed in six patients (54.5%) at post-operative week 2. There were no surgery-related deaths or cerebrospinal fluid leaks. Postoperative intracranial infection was observed in one patient (9.1%), and during the follow-up period, tumor recurrence occurred in one patient (9.1%). Conclusion The expanded TLTA provides a feasible suprachiasm corridor to remove tumors extending into the third ventricle, especially for craniopharyngiomas. Sound understanding of the major strengths and limitations of this approach, as well as strategies for complication avoidance, is necessary for its safe and effective application.